グラフィック ディスプレイ オ モチイタ カイワ ガタ スペクトル カイセキ システム - 岩渕, 美代子; イワブチ, ミヨコ; 藤井, 良一; フジイ, リョウイチ; 内海, 達郎; ウツミ, タツロウ; IWABUCHI, Miyoko; FUJII, Ryoichi; UTSUMI, Tatsuro (国立極地研究所, 1978)
P(論文) 南極観測で得られた各種波動データで地磁気脈動,自然電磁波,地震波,気候諸変動等のデータ)を効率よく解析するために,国立極地研究所の電子計算機M-160 IIおよびその周辺機器であるグラフィックディスプレイ端末を利用した会話型スペクトル解析システムの開発を行った.このシステムの特徴は,(1)ディスプレイ上のデータを見ながら自由に解析区間を選べること, (2)スペクトル解析機能およびその前処理としてのフィルター処理機能を有し,結果を見ながら何回でも繰り返し行えること,(3)表示の種類が豊富で必要に応じていつでもハードコピーがとれること等である.1次元および2次元データを対象とし,スペクトル解析の手法としては, Blackman-Tukey法,FFT法,MEM法を,フィルターとしては,チェビシェフのhigh-pass, low-pass, band-passおよびband-rejectを用意した.ここでは,システムの概要とテストデータに対するスペクトル解析結果およびフィルター結果を示し,その検討を行う. The spectral analysis system was made by the use of the computer HITAC M-160 II and the graphic display terminal, in order to analyze efficiently various kinds of wave data observed by Antarctic research, such as magnetic pulsations, natural electromagnetic waves, seismological waves and meteorological phenomena. The largest merit of the system is that it can analyze one- or two-dimensional time series data trial and error by the use of graphic display terminal. From the long original data one can choose easily a part of data for analysis, and freely use several kinds of filters and spectral methods. Generally used spectral methods, Blackman-Tukey, Fast Fourier Transform and Maximum-Entropy Method and the Chebyshev-filters, high-pass, low-pass, band-pass and band-reject are usable. In this paper, the system is outlined, and the spectral and filtered results of the test data are given and discussed. departmental bulletin paper